The peroxisome proliferator-activated receptor-β/δ antagonist GSK0660 mitigates retinal cell inflammation and leukostasis. (January 2020) - Capozzi, Megan E.; Savage, Sara R.; McCollum, Gary W.; Hammer, Sandra S.; Ramos, Carla J.; Yang, Rong; Bretz, Colin A.; Penn, John S.
Abstract: Diabetic retinopathy (DR) is triggered by retinal cell damage stimulated by the diabetic milieu, including increased levels of intraocular free fatty acids. Free fatty acids may serve as an initiator of inflammatory cytokine release from Müller cells, and the resulting cytokines are potent stimulators of retinal endothelial pathology, such as leukostasis, vascular permeability, and basement membrane thickening. Our previous studies have elucidated a role for peroxisome proliferator-activated receptor-β/δ (PPARβ/δ) in promoting several steps in the pathologic cascade in DR, including angiogenesis and expression of inflammatory mediators. Furthermore, PPARβ/δ is a known target of lipid signaling, suggesting a potential role for this transcription factor in fatty acid-induced retinal inflammation. Therefore, we hypothesized that PPARβ/δ stimulates both the induction of inflammatory mediators by Müller cells as well the paracrine induction of leukostasis in endothelial cells (EC) by Müller cell inflammatory products. To test this, we used the PPARβ/δ inhibitor, GSK0660, in primary human Müller cells (HMC), human retinal microvascular endothelial cells (HRMEC) and mouse retina. We found that palmitic acid (PA) activation of PPARβ/δ in HMC leads to the production of pro-angiogenic and/or inflammatory cytokines that may constitute DR-relevant upstream paracrine inflammatory signals to EC and other retinal cells. Downstream, EC transduce these signals and increase their synthesis and release of chemokines such as CCL8 and CXCL10 that regulate leukostasis and other cellular events related to vascular inflammation in DR. Our results indicate that PPARβ/δ inhibition mitigates these upstream (MC) as well as downstream (EC) inflammatory signaling events elicited by metabolic stimuli and inflammatory cytokines. Therefore, our data suggest that PPARβ/δ inhibition is a potential therapeutic strategy against early DR pathology. Highlights: The PPARβ/δ inhibitor GSK0660 inhibits palmitic acid-stimulated inflammatory mediator production by Müller cells. GSK0660 inhibits TNFα-induced leukocyte adhesion in both HRMEC and mouse retina. GSK0660 blocks TNFα-induced leukostasis by modulating the levels of CCL8 and CXCL10. GSK0660's effects on retinal cells are mediated by both PPARβ/δ-dependent and PPARβ/δ-independent pathways.